Effect of modification with FeCl3 and MgCl2 on adsorption characteristics of woody biochar - Chemerys, Valeriia; Baltrėnaitė, Edita (International Conference “Environmental Engineering”, 2017)
Due to high specific surface area, well-developed porous structure and surface functionality biochar has a potential for being used as low-cost adsorbent for adsorption of organic and inorganic contaminants from aqueous solutions. Higher adsorption capacity and selectivity for metals could be further developed after modification of proper ties of biochar through physical (“designed biochar”) and chemical (“engineered biochar”) modification techniques. Wood waste of three types [aspen (Populus tremula L.), pine (Pinus sylvestris L.) and fir (Picea abies L.)] were selected to produce the biochar under slow pyrolysis conditions at 450 °C for 2 h with the heating rate of 10 °C/min. Mg and Fe articles, acting as potential sorption sites for adsorption of metals, were added into the biochar through modification of the biochar with metal salts MgCl2 and FeCl3. The aim of the study was to investigate the effect of chemical modifications of woody biochar with MgCl2 and FeCl3 on the adsorption characteristics of the biochar. The engineered biochar with improved physico-chemical and sorptive properties was evaluated as potential adsorbent of metals from aqueous solutions. Such characteristics of the biochar, as density, porosity, pH, cation exchange capacity, electrical conductivity, moisture content, ash content, water holding capacity, total organic carbon were analyzed. Modifications followed by increasing of moisture and ash content. While carrying out the future adsorption experiment, significantly decreased pH and electrical conductivity of the engineered biochar should be taken into account. Increased cation exchange capacity of the engineered biochar promotes enhanced adsorption of metals.